พฤติกรรมผู้บริโภควัยทำงานในกรุงเทพมหานครต่อการบริโภคขนมไทย - ณภัคอร สงวนตั้ง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to explore ehavior of working-aged consumers in Bangkok Towards consuming Thai desserts . Questionnaires were used as the tool to collect data from 300 officers in business and government sectors, whose offices were located in office buildings in Bangkok, according to the quota sampling method. The respondents were classified into 3 groups according to the ranges of age: 100 respondents in 20-29 years old, 100 respondents in 30-39 years old, and 100 respondents in 40-60 years old. Data were distributed and analyzed by frequency, percentage, and mean. The results of the studies on consumer behavior and marketing mix factors revealed that the group of officers whose ages were between 20-60 years and who purchased Thai dessert consisted of female with bachelor’s degree. The people in this group worked in the positions of head/owner/administrator and operation officer/maid in the similar proportion. Most of them purchased fresh Thai dessert, especially streamed/boiled/stirred types of dessert. The most preferable Thai dessert was the one that made from natural ingredients; following by the traditional dessert and the healthy dessert, accordingly. Elements of product factor that influenced their purchasing decision at the highest level were good taste, cleanliness and freshness, respectively. They mostly purchased it for self-consumption. They mostly made purchasing decision by themselves. Prior to purchase, the majority did not do the information search; but some of them tasted products and got recommendation from friends or fellows, accordingly. Most of them did the comparison before purchase. They mostly purchased the studied product on Saturday and Sunday; followed by Monday to Friday, during 12.01-13.30 hrs., 09.00-12.00 hrs., and after 16.00 hrs., accordingly. The frequency of purchasing Thai dessert was 1-2 times per week; followed by 1-2 times per month, and according to special occasion, respectively. Elements of promotion factor that influenced their purchasing decision at high level were to have free trail piece of product, and to be recommended or to be shared by others such as friends, famous tasters, and Internet, respectively. The most preferable or convenient location where the customers purchased the Thai dessert was Thai dessert shops; followed by fairs/markets at their offices because these places were located nearby their residence or workplace. Most of them purchased the studied product from a single regular shop; followed by 2-3 regular shops. Elements of place factor that influenced their purchasing decision at high level were clean and beautiful shop, to have full stock of products to be sold, appropriate service hours as needed, easy location to access, convenient location where was located near residence, easy for transportation, and near workplace, and to have parking space, respectively. In each time of purchase, they spent at less than 150 Baht for Thai dessert. Elements of price factor that influenced their purchasing decision at high level were reasonable price comparing to its ingredients, to have clear price tag, reasonable price comparing to its size, price variety, and reasonable price comparing to its beauty, respectively. In addition, the results also showed that marketing mix factors affecting the purchase of Thai dessert at high level were price, place, and product; while the promotion factor affected the purchase of Thai dessert at moderate level. Suggestion on Thai dessert was given to the effort to retain product’s taste, ingredients, feature, and uniqueness authentic.